Influence of Islamic Education Teachers Competency on Practice of Higher Order Thinking Skills - Hamidon, Mas; Johari Sihes , Ahmad (International Journal of Academic Research in Progressive Education and Development, 2020)
Higher Order Thinking Skill (HOTS) has become a demanded approach in education because it is one of the skills in the 21st century. This conceptual paper was motivated by the belief that teachers with high level of professional competency will be able to produce students who are competent and adaptable to changes in their surroundings. This concept paper aims to discuss the influence of Islamic Education teachers competency on HOTS teaching practices. The three domains of teacher competence namely knowledge, skills and personality of teachers seems to have significant impact on teaching practice of high level thinking skills. The concept paper reveals that teachers' ability in integrating and developing thinking skills in teaching their subjects is strongly related to teacher competency. Therefore, the objectives of teaching for developing HOTS in students would be difficult if the teachers are not fully competent to use it. Nevertheless, the discussion of this conceptual paper can be used as recommendations for practice change with regard to HOTS development.